REACTIONS FORMING SMYTHITE, FE9S11 - Furukawa Y.; Barnes H.L. (My University, 1996)
This study evaluates the processes that form smythite, a mineral associated normally either with siderite in sedimentary iron formations and hydrothermal carbonate veins, or with pyrrhotite in nickel sulfide ore deposits. Smythite was found to form via either of two processes, the replacement of siderite in low temperature aqueous environments as proposed by Rickard (1968) or exsolution from high-temperature, S-rich pyrrhotite during cooling as proposed by Fleet (1982).In solutions with pH > 6 at temperatures below 53°C, surface-bound Fe2+ reacts with aqueous sulfide on the siderite surface to form smythite. On the other hand, in low pH sulfide solutions with little dissolved CO2, siderite dissolves rapidly yielding free Fe2+ and saturates the bulk solution with amorphous Fe(HS)2. Amorphous Fe(HS)2 is subsequently replaced by mackinawite and then by pyrite but not smythite.When S-rich (less than #46 Fe atomic %) hexagonal pyrrhotite 1C is cooled slowly from 500°C or higher, it re-equilibrates to an assemblage that is stable at low temperature (S-poor pyrrhotite + pyrite). However, if cooling is rapid (several hundred °C/s), in the absence of local pyrite grains, pyrite does not exsolve owing to its slow nucleation. Because smythite is structurally similar to pyrrhotite, its nucleation is possible during such rapid cooling thereby balancing the bulk composition of the system without pyrite exsolution. Smythite exsolution occurs only in a pyrite-free environment because pyrite overgrowths can occur if pre-existing pyrite is present for nucleation. This eliminates the need for metastable exsolution of smythite to achieve a mass balance for sulfur. Pyrrhotite containing some Ni (1.6 # 2.9 atomic %) exsolves smythite during slower cooling because Ni retards the equilibrium exsolution of pyrite.